ICT System in Supply Chain Management for Research in Higher Education Institute - Chansamut, Artaphon (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2018)
This article, an ICT System Supply Chain Management for Research in Higher Education Institutes, is to present education management through a supply chain. It is aimed to provide a more effective education management, approach which is appropriate for changes in the globalized economy and society. The process consists of research suppliers, manufacturers, customers, and consumers, all connected with information communication technology to the educational institute through the supply chain management. This truly adds value to the educational institute as a production source providing satisfactory product research for the consumers as planned. A supply chain designed like this will be applicable for effective education management.